2020
DOI: 10.1111/raq.12488
|View full text |Cite
|
Sign up to set email alerts
|

Availability and usefulness of economic data on the effects of aquaculture: a North Atlantic comparative assessment

Abstract: This paper focuses on the availability of economic indicators and metrics to assess effects of marine aquaculture production in the North Atlantic area (the EU, Norway, Canada and USA), including also social and environmental effects. We consider how aquaculture planning and management is organised in the different countries and the usefulness of economic information to address different aquaculture-related policies. We find that the most relevant economic data for aquaculture management should be at the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In addition to environmental data used for environmental models, in planning and licensing it can also be relevant to have economic data. Combining economic impacts like employment and income for the wider society, with economic data on environmental impact, like valuations, can make comparisons and trade‐off decisions easier and more transparent 260 . Mikkelsen et al 260 showed the availability of relevant economic data on aquaculture.…”
Section: Review Of Research Articles and Academic Studiesmentioning
confidence: 99%
“…In addition to environmental data used for environmental models, in planning and licensing it can also be relevant to have economic data. Combining economic impacts like employment and income for the wider society, with economic data on environmental impact, like valuations, can make comparisons and trade‐off decisions easier and more transparent 260 . Mikkelsen et al 260 showed the availability of relevant economic data on aquaculture.…”
Section: Review Of Research Articles and Academic Studiesmentioning
confidence: 99%
“…NbS Criterion 4 brings up the discussion of what may be considered a truly viable economic aquaculture system that considers social issues (Hughes, 2021), although the terms "inclusiveness" and "equity" are not explicitly mentioned in the Criterion's indicators. Criterion 4 also implies that positive and negative externalities must be fully identified and measured despite the difficulty of doing so due to insufficient economic data, in particular at a sub-national level (Mikkelsen et al, 2021). This also means going beyond conventional micro-and macro-economic and financial indicators (e.g., gross and net incomes, accountable added value, and Gross Domestic Profit (Costanza et al, 2016)).…”
Section: What Is the Economic Viability Of Aquaculture Operationsmentioning
confidence: 99%
“…Overall, complex social-ecological interactions and context specificity make the social and economic impacts of aquaculture difficult to predict, 90,91 and adding to that difficulty, economic data on the effects of aquaculture is not available at the local scale in many regions. 97 The complex reality of the impact of aquaculture at multiple scales is not well reflected in eco-certification criteria. Although some criteria include far-field considerations directly (e.g., considering the effects of fish escapes) 35,98 and indirectly (e.g., promoting coordination amongst producers), 35 aquaculture eco-certification largely focuses on farm-scale criteria and lacks ecosystem perspectives.…”
Section: Accounting For the Scale Of Aquaculture Effectsmentioning
confidence: 99%
“…For example, when food security is prioritised globally, maximising production to meet this demand puts pressure on local systems. Overall, complex social–ecological interactions and context specificity make the social and economic impacts of aquaculture difficult to predict, 90,91 and adding to that difficulty, economic data on the effects of aquaculture is not available at the local scale in many regions 97 …”
Section: Challenges and Solutions For Aquaculture Eco‐certificationmentioning
confidence: 99%